Absolute and allometrically scaled peak force during tests of isometric strength and power in young male athletes at different stages of maturity - Dobbs, I.; Wong, M.; Lloyd, R.; Oliver, J. (The Journal of Strength and Conditioning Research, 2021)
Purpose: Literature has reported that more mature athletes tend to display greater absolute strength and power than younger athletes primarily due to the influence of increased body mass (3, 5, 6). To control for the influence of body mass on peak force (PF) production, it has been suggested to use allometric scaling methods (4, 6). Allometric scaling provides a normalized methodological approach for performance tests (2) and has been previously used to compare isometric strength measures for youth of different maturity status (1). Brownlee et al. (1) reported significant increases with maturity between groups of youth soccer players that were pre-, circa-, and post- peak height velocity (PHV). However, there is little research available on the difference between maturity groups on scaled PF for power in the counter movement jump (CMJ) and squat jump (SJ). Methods: One-way analysis of variance (ANOVA) with post-hoc analysis was used to determine the differences between 3 maturity groups (pre-, circa- and post-PHV) for absolute peak force (PFabs) and allometrically scaled peak force (PFallo) in the IMTP, SJ, and CMJ. Effect sizes (Cohen's d) were calculated to interpret the magnitude of differences between-group. Regression slopes were conducted for each maturity group for PFabs and PFallo from the IMTP, SJ, and CMJ test using maturity status as a covariate. Linear regression slopes were created for the given variables within each maturity group to describe rate of change. Results: Analysis for all tests and between between-group comparisons are displayed in Table 1. PFabs and PFallo showed significant increases with advancing maturity in all tests (p < 0.05). Moderate to very large differences were observed between the pre- vs. circa-PHV groups and only moderate differences between the circa- vs. post-PHV groups for PFabs and PFallo in all tests. Large to very large differences were observed in PFabs and PFallo between the pre- vs. post-PHV groups in all tests (p < 0.05). Regression slope analyses revealed the circa-PHV group were always experiencing the greatest rate of change for PFabs and PFallo in all tests (p > 0.05) (Figure 1). The high variability within this group meant the rates of change were non-significant between-groups (p > 0.05); however, slopes for IMTP PFabs (p = 0.069), SJ PFabs (p = 0.063) and SJ PFallo (p = 0.080) were approaching significance. Conclusions: Advanced maturity resulted in significant improvements for PFabs and PFallo in the IMTP, SJ, and CMJ, suggesting that adaptations to force producing qualities accompany natural physical growth and development. The data indicates the largest differences in strength and lower body power occur around the adolescent growth spurt, based on the consistently larger effect sizes between the pre- vs. circa-PHV groups. The rates of change of were non-significant between groups, however, the regression slopes suggest that greater changes occur within the circa-PHV period which aligns with the pubertal spurt. The circa-PHV group was a period associated with greatest rate of change along with the greatest amount of variability. Practical Applications: Owing to the natural development of strength and power qualities, practitioners should be cognizant of the individualized rates of adaptation for youth males around the pubertal spurt and its interaction with training.